Pravna ureditev oblik sodobnega suženjstva s poudarkom na trgovini z ljudmi in prisilnem delu - Lajlar, Lina (Podjetje in delo, 2022)
The article presents selected aspects of the topic of modern (contemporary) slavery. As the topic is extensive, only human trafficking and forced labour will be described in detail. In this article we note that modern forms of slavery appear in various forms, which are constantly changing (especially due to the rapid social changes and digitalisation). Therefore, it is very difficult to recognise modern forms of slavery and they are (too) often overlooked. International legal documents dating back to 1926 define slavery, but only in its "classical", i.e. "historical" form. The problem therefore arises with the definition of the concept of "modern slavery", which remains undefined in international law. The next finding is that the legal sources that define classical forms of slavery can serve as a basis for creating a definition of modern slavery, albeit appropriately adapted to modern times (in addition to law, we must consider other fields such as sociology, history and economics). Only a clear definition of the term in international law allows the perpetrators to be prosecuted and victims to be adequately reimbursed. The next finding presented in the article is that companies also play a key role in preventing modern slavery. They have a responsibility to ensure that their supply chains do not contain products of slave labour. In Slovenia, 20 companies have already joined the Commitment to Respect Human Rights in Business (at the time of writing this article), which is, in the author's opinion, a good initial step in the fight against modern slavery.
Keywords: forced labour; Guiding Principles on Business and Human Rights; human trafficking; modern forms of slavery; Nacionalni akcijski načrt; National Action Plan; prisilno delo; slavery in supply chains; Smernice OZN za spoštovanje človekovih pravic v gospodarstvu; sodobne oblike suženjstva; suženjstvo v nabavnih verigah; trgovina z ljudmi